Black Gram and its Production Constraints - Saithala, Mounika; Naik, M. Ramesh; Teja, R. Ravi (Chronicle of Bioresource Management, 2020)
Black gram (Vigna mungo) is a crucial pulse crop, renowned for its high nutritional value and economic significance, particularly in India, contributing to approximately 70% of the global production. Despite its pivotal role in the pulse economy, black gram cultivation is plagued by several production constraints. Challenges include moisture stress, pre-harvest sprouting, non-synchronous ripening, low seed replacement rates, along with poor soil fertility, high-temperature stress, soil salinity problems, and susceptibility to pests and diseases. These issues are compounded by erratic climate patterns that further jeopardize yield stability. To secure the future of black gram production, a multifaceted strategy is essential one that integrates advanced agronomic practices, improved irrigation and input management, enhanced seed quality and the development of high-yielding climate-resilient varieties. Implementing region-specific measures based on empirical data can boost productivity, enhance economic returns, and ensure food security for pulse-dependent farming communities in the face of ever-evolving agro-climatic challenges.